2020
DOI: 10.3390/jcm9020534
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Thyroiditis is Associated with HLA-B*18:01, -DRB1*01 and -C*04:01—The Significance of the New Molecular Background

Abstract: Subacute thyroiditis (SAT) is a thyroid inflammatory disease whose pathogenesis is still not completely defined. Previous viral infection is considered to be a triggering factor in genetically predisposed individuals. In about 70% of patients, susceptibility to SAT is associated with the HLA-B*35 allele. The correlation between SAT and other human leukocyte antigens (HLA) has not yet been unequivocally demonstrated and the genetic background is still unknown in about 30% of patients. The purpose of our study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 28 publications
2
58
0
2
Order By: Relevance
“…Recent improvement of diagnostic methods brought the novel insight into the genetic background. In 2020, our research team demonstrated the new association between HLA and SAT in the Caucasian population [ 10 ]. In addition to the previously described correlation with HLA-B*35 , SAT was proved to be associated with the presence of HLA-B*18:01, -DRB1*01 and -C*04:01 [ 10 ].…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Recent improvement of diagnostic methods brought the novel insight into the genetic background. In 2020, our research team demonstrated the new association between HLA and SAT in the Caucasian population [ 10 ]. In addition to the previously described correlation with HLA-B*35 , SAT was proved to be associated with the presence of HLA-B*18:01, -DRB1*01 and -C*04:01 [ 10 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…In 2020, our research team demonstrated the new association between HLA and SAT in the Caucasian population [ 10 ]. In addition to the previously described correlation with HLA-B*35 , SAT was proved to be associated with the presence of HLA-B*18:01, -DRB1*01 and -C*04:01 [ 10 ]. In Caucasians, HLA-C*04:01 is in a linkage disequilibrium with HLA-B*35:01/02/03 , i.e.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Für eine (post-)virale Genese spricht auch, dass die SAT in vielen Fällen nach Infekten der oberen Atemwege auftritt, wobei die Latenz üblicherweise zwischen 2 und 8 Wochen beträgt [10]. In der Pathogenese der SAT dürfte außerdem auch eine gewisse genetische Prädisposition eine Rolle spielen, da in bis zu 70 % der Fälle eine Assoziation mit HLA-B35 besteht [11]. Durch die entstehende Inflammation kommt es zu einer Beschädigung der Schilddrüsenfollikel sowie zu einer Proteolyse des in den Schilddrüsenfollikeln gespeicherten Thyreoglobulins.…”
Section: Subakute Thyreoiditis (Thyreoiditis De Quervain Granulomatöunclassified
“…2,3 More recent investigations have uncovered an association with the presence of additional antigens, namely, HLA-B*18:01, DRB1*01, and HLA-C*04:01. 4 The annual reported age-and sex-adjusted incidence is 4.9 patients per 100,000 population. 5,6 The distinctive clinical picture includes typical viral symptoms, such as malaise, fever, and myalgias.…”
mentioning
confidence: 99%